2022
DOI: 10.3389/fphar.2022.850583
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Lithium Treatment in SARS-CoV-2 Infected Patients

Abstract: At the beginning of the pandemic, we observed that lithium carbonate had a positive effect on the recovery of severely ill patients with COVID-19. Lithium is able to inhibit the replication of several types of viruses, some of which are similar to the SARS-CoV-2 virus, increase the immune response and reduce inflammation by preventing or reducing the cytokine storm. Previously, we published an article with data from six patients with severe COVID-19 infection, where we proposed that lithium carbonate could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…61,62 Lithium was also associated with reduced hospitalization days, need for intensive care unit admission, and death. 62 Beyond Clozapine REMS: Risks Overshadowed?…”
Section: Risk Evaluation and Mitigation Strategy Covid-19 And The Nex...mentioning
confidence: 97%
See 1 more Smart Citation
“…61,62 Lithium was also associated with reduced hospitalization days, need for intensive care unit admission, and death. 62 Beyond Clozapine REMS: Risks Overshadowed?…”
Section: Risk Evaluation and Mitigation Strategy Covid-19 And The Nex...mentioning
confidence: 97%
“…Lithium, which has been used to counteract clozapine-associated neutropenia, was recently reported in an RCT to alter inflammatory activity and immune response during COVID-19 infection 61,62 . Lithium was also associated with reduced hospitalization days, need for intensive care unit admission, and death 62 …”
Section: Clozapine and Remsmentioning
confidence: 99%
“…Lithium has also been proposed as a treatment option in COVID-19 as it exerts both antiviral and immunomodulatory effects. 24 Preclinical studies have demonstrated that lithium can inhibit replication of various types of viruses including those belonging to coronavirus family. 25 The antiviral mechanisms of lithium are thought to be related to inhibition of phosphatidylinositol signaling pathway, regulation of autophagy, and inhibition of glycogen kinase-3 isoform.…”
Section: Neutrophilic Properties Of Lithium and Its Implications In C...mentioning
confidence: 99%
“…Lithium has also been proposed as a treatment option in COVID‐19 as it exerts both antiviral and immunomodulatory effects 24 . Preclinical studies have demonstrated that lithium can inhibit replication of various types of viruses including those belonging to coronavirus family 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation